Chromium and Aluminum Phytotoxicity in Maize: Morpho‐Physiological Responses and Metal Uptake. Issue 8 (31st May 2016) - Anjum, Shakeel Ahmad; Ashraf, Umair; Khan, Imran; Tanveer, Mohsin; Ali, Muqarrab; Hussain, Imtyaz; Wang, Long Chang
Abstract : The present study investigated the uptake, translocation, and accumulation of chromium (Cr 6+ ) and aluminum (Al 3+ ) in maize and their induced variations in morpho‐physiological and biochemical attributes as well as growth behavior and yield formation. Plants were grown in pots supplied with heavy metals, alone and in combination (chromium (Cr), aluminum (Al) and chromium + aluminum (Cr + Al)) while pots without adding Cr or Al were regarded as control. Metal stress considerably reduced growth and yield related attributes as well as photosynthetic pigments of maize. However, production of hydrogen peroxide (H2 O2 ), thiobarbituric acid and activities of ascorbate peroxidase, glutathione reductase, glutathione peroxidase, and ascorbic acid were substantially increased under Cr and Al stress. A significant increase in soluble sugars and total phenolic contents were recorded in plants exposed to Cr and Al stress. Furthermore, all physiological attributes were increased with plant age except chlorophyll. Interestingly, Cr alone was proved more toxic to maize than Al alone. Cr and Al accumulation varied significantly ( p ≤ 0.05) among different plant organs as roots > stem > leaves > corn ear > grains, whereas degrees of translocations were higher from stem to other plant parts than roots to stem. Accumulation of Cr and Al in either above‐ or below‐ground plant parts are negatively correlated with grains and biological yield. The overall trend of metal stress on plant growth and yield were perceived as: Cr + Al > Cr > Al > control. Furthermore, synergistic effects of Cr + Al were more prominent than the individual effects of Cr and Al alone. Abstract : Both chromium and aluminum negatively affect maize growth, yield, and photosynthetic pigments. Enhanced soluble sugars, total phenolic contents, and anti‐oxidant activities (APX, GR, and GPX) provide protection against reactive oxygen species (ROS)‐induced oxidative damage under Cr and Al stress. Further, the metal contents in different maize organs are recorded as: roots > stem > leaves > corn ear > grains.